Olaparib Addition to Maintenance Bevacizumab Therapy in Ovarian Carcinoma With BRCA-Like Genomic Aberrations - Schouten, Philip C. (JAMA Network, 2025)
Importance: Testing for homologous recombination deficiency is required for the optimal treatment of high-grade epithelial ovarian cancer. The search for accurate biomarkers is ongoing.
Objective: To investigate whether progression-free survival (PFS) and overall survival (OS) of patients with high-grade epithelial ovarian cancer treated with maintenance olaparib or placebo differed between patients with a tumor BRCA-like genomic profile and patients without a tumor BRCA-like profile.
Design, setting, and participants: This cohort study was a secondary analysis of the PAOLA-1 randomized clinical trial that compared olaparib plus bevacizumab with placebo plus bevacizumab as maintenance treatment in patients with advanced high-grade ovarian cancer after a good response to first-line platinum with taxane chemotherapy plus bevacizumab, irrespective of germline or tumor BRCA1/2 mutation status. All patients with available tumor DNA were included in the analysis. The current analysis tested for an interaction between BRCA-like status and olaparib treatment on survival outcomes. The original trial was conducted between July 2015 and September 2017; at the time of data extraction for analysis in March 2022, a median follow-up of 54.1 months (IQR, 28.5-62.2 months) and a total follow-up time of 21 711 months was available, with 336 PFS and 245 OS events.
Exposures: Tumor homologous recombination deficiency was assessed using the BRCA-like copy number aberration profile classifier. Myriad MyChoice CDx was previously measured. The trial was randomized between the olaparib and bevacizumab and placebo plus bevacizumab groups.
Main outcomes and measures: This secondary analysis assessed hazard ratios (HRs) of olaparib vs placebo among biomarker strata and tested for interaction between BRCA-like status and olaparib treatment on PFS and OS, using Cox proportional hazards regression.
Results: A total of 469 patients (median age, 60 [range 26-80] years) were included in this study. The patient cohort consisted of women with International Federation of Gynaecology and Obstetrics stage III (76%) high-grade serous (95%) ovarian cancer who had no evaluable disease or complete remission at initial or interval debulking surgery (76%). Thirty-one percent of the tumor samples (n = 138) harbored a pathogenic BRCA mutation, and BRCA-like classification was performed for 442 patients. Patients with a BRCA-like tumor had a longer PFS after olaparib treatment than after placebo (36.4 vs 18.6 months; HR, 0.49; 95% CI, 0.37-0.65; P < .001). No association of olaparib with PFS was found in patients with a non-BRCA-like tumor (17.6 vs 16.6 months; HR, 1.02; 95% CI, 0.68-1.51; P = .93). The interaction was significant (P = .004), and HRs and P values (for interaction) were similar in the relevant subgroups, OS, and multivariable analyses.
Conclusions and relevance: In this secondary analysis of the PAOLA-1 randomized clinical trial, patients with a BRCA-like tumor, but not those with a non-BRCA-like tumor, had a significantly longer survival after olaparib plus bevacizumab treatment than placebo plus bevacizumab treatment. Thus, the BRCA1-like classifier could be used as a biomarker for olaparib plus bevacizumab as a maintenance treatment.